2019
DOI: 10.1039/c9ra05833h
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dynamic fatigue crack propagation properties and viscoelasticity of natural rubber/silicone rubber composites

Abstract: The successfully established relationship between dynamic fatigue crack propagation behaviour and viscoelasticity of NR/VMQ composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
(47 reference statements)
1
14
0
Order By: Relevance
“…In addition, the small dark particles enclosed by yellow boxes in both TEM and AFM images of T0-D0, for instance, refer to the premixed silica in the VMQ/silica masterbatch, and it is worth noting that some of them have migrated from the internal VMQ domains into the NR matrix after compounding. This could be explained in terms of the interfacial adhesive energy (W rf ) 26 and wetting coefficient (ω NR-VMQ ) 9,27,28 by the results listed in Table S1: the higher W rf of NR−silica compared to VMQ−silica indicates stronger interfacial interactions between the NR phases and silica; ω NR-VMQ > 1 demonstrates selective distribution tendency of silica in the NR phases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the small dark particles enclosed by yellow boxes in both TEM and AFM images of T0-D0, for instance, refer to the premixed silica in the VMQ/silica masterbatch, and it is worth noting that some of them have migrated from the internal VMQ domains into the NR matrix after compounding. This could be explained in terms of the interfacial adhesive energy (W rf ) 26 and wetting coefficient (ω NR-VMQ ) 9,27,28 by the results listed in Table S1: the higher W rf of NR−silica compared to VMQ−silica indicates stronger interfacial interactions between the NR phases and silica; ω NR-VMQ > 1 demonstrates selective distribution tendency of silica in the NR phases.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the dynamic fatigue crack propagation behavior of NR/VMQ composites was studied, and a connection between crack growth rate (dc/dN) and viscoelasticity of rubber has been extensively explored based on our previous work. 9 The results could be significant for designing rubber composites with an extended service life for dynamic products as the nucleation and propagation of cracks under long-term cyclic loading conditions would cause fatigue failure. 20 the side-dangling vinyl groups in VMQ with less steric hindrance would exhibit a higher reactivity with TMPMP compared to the double bonds in NR, which are in the main chain.…”
Section: Introductionmentioning
confidence: 99%
“…First, for exploring the reason of inhomogeneous silica dispersion in VMQ/BR composites, the two-phase morphology of VMQ-silica master-batch/BR blends has been observed via AFM and TEM 15 in Fig. 3.…”
Section: Phase Morphologymentioning
confidence: 99%
“…In our previous studies, VMQ/SBR blends were prepared, which focus on investigations of strengthening interfacial compatibility 13 and rubber-ller interaction; 14 besides, dynamic fatigue crack propagation behaviour of VMQ/NR composites was also studied. 15 Here, VMQ was applied to improve anti-aging properties of BR, further to reduce the dosage of antioxidants and prevent product surface discoloration. As for microscopic morphology would greatly inuence macroscopic properties of composites, the two-phase structure of VMQ-silica master-batch/BR and distribution of ller were further investigated via atomic force microscopy (AFM) and transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, VMQ/functionalized graphene (FG) foams also exhibited improvements in tensile strength (130%) and the corresponding elongation at break (140%) compared to VMQ/chemical reduction graphene (rGO) foams [7]. In addition, the results also showed that more addition of VMQ could improve crack propagation resistance of natural rubber (NR)/VMQ [8].…”
Section: Introductionmentioning
confidence: 99%